An Evaluation of the Contributions and Prospects of Road Taxes to Total Tax Collections by States in Nigeria 2010-2022 - Sani Mohammed; Sunusi Garba; Sunusi Sa’ad Ahmad; Muhammad Muhammad Sallau; Babangida Mohammed Auwal; Yusuf Abdu Gimba (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
The 36 federating states of Nigeria have a persistent paucity of funds for the provision of public goods and services for the citizens. However, this came when the Taxes and Levies Approved List for Collection Act 1998 availed the states of eleven different taxes, which, if properly harnessed, could alleviate the financial difficulties. Therefore, this study aims to longitudinally evaluate the contributions of road taxes, which are one of the taxes collected by states in Nigeria. To achieve this aim, data on collection from state road taxes was collected from the National Bureau of Statistics 2010-2022 annual reports. Descriptive statistical tools of tables, charts, and percentages are utilized in analyzing collected data, while a public policy analytical framework underpinned the study. Results from the study revealed that road taxes are making moderate contributions to total taxes collected by states. Therefore, if the states could strengthen policies, laws and regulations on road taxes, it could greatly enhance their total collections from taxes. The policy implication of this finding is that road taxes as a public policy impact taxes collected by states even though insignificant; therefore, policymakers should strengthen this policy for national development